Deciphering the Potential Role of Symbiotic Plant Microbiome and Amino Acid Application on Growth Performance of Chickpea Under Field Conditions - Rafique, Munazza; Ali, Abid; Naveed, Muhammad; Abbas, Tasawar; Al-Huqail, Asma A.; Siddiqui, Manzer H.; Nawaz, Ahmad; Brtnicky, Martin; Holatko, Jiri; Kintl, Antonin; Kucerik, Jiri; Mustafa, Adnan (Frontiers in Plant Science, 2022)
Food production systems must be upgraded in order to sustain production with low cost and slow land degradation. Using rhizobial inoculants and amino acids may present more effective, safer, economical, and sustainable alternative means of realizing higher productivity of crops. This study investigated the possibility of using Rhizobium and L-methionine together to boost chickpea production. The field experiments were performed on chickpea for two succeeding years using Rhizobium and L-methionine (at three levels i.e., 5, 10 and 15 mg L-1) separately and in combination. These treatments substantially increased growth and yield of chickpea in comparison to untreated plants. Though, there was higher response of plants to lower dose of L-methionine i.e., 5 mg L-1. Maximum production (39.9 and 34.5% in first and second year, respectively) of chickpea was obtained with combined use of Rhizobium and lower level of L-methionine. This treatment was also the most effective in improving N and P content of plants. Photosynthetic pigments and seed chemical composition were also significantly improved with Rhizobium inoculation. However, these effects were prominent when Rhizobium inoculation was accompanied by L-methionine. Hence, the potential of combined use of L-methionine and Rhizobium inoculation may be utilized to develop sustainable production system for chickpea.